0622 Solriamfetol (JZP-110) in the Treatment of Excessive Sleepiness in Narcolepsy and Obstructive Sleep Apnea: Maintenance of Wakefulness Test Results Across the Day. (27th April 2018) - Schweitzer, P K; Strohl, K P; Malhotra, A; Rosenberg, R; Sangal, R; Zee, P C; Thomas, R; Chen, D; Li, J; Carter, L P; Lee, L; Black, J; et al.
Abstract: Introduction: Two phase 3 trials in adults with excessive sleepiness (ES) and narcolepsy or ES and obstructive sleep apnea (OSA) demonstrated robust wake-promoting effects of solriamfetol with significant increase in overall mean sleep latency (MSL; mean of first 4/5 trials) on the 40-minute Maintenance of Wakefulness Test (MWT). Further analyses were performed to evaluate the effects of solriamfetol across the day at each MWT trial after morning dosing. Methods: Participants were randomized to placebo or solriamfetol 37.5 (OSA only), 75, 150, or 300 mg. Only doses with significant least squares mean (standard error) (LS mean [SE]) change from baseline to week 12 in overall MSL and Epworth Sleepiness Scale (co-primary endpoints) were considered efficacious and tested further for efficacy time course at each MWT trial (MWT1: 1-hour, MWT2-5: 2-hour consecutive intervals post-dose). The first trial with significant change ( P <0.05) was identified and testing to the next trial was performed until non-significance or MWT5. Results: Solriamfetol (75 [OSA only], 150, and 300 mg) demonstrated significant change from baseline in MSL at all MWT trials (≈ 9 hours post-dose). Narcolepsy MWT1: 150 mg 9.9* (1.7), 300 mg 9.9* (1.8), placebo -0.6 (1.7) through MWT5: 150 mg 9.3* (1.9), 300 mg 12.2* (2.0), placebo 3.1 (1.8); OSA MWT1: 75 mg 5.8* (1.8), 150 mg 10.9* (1.3), 300 mg 12.5* (1.4), placebo -0.4 (1.3) through MWT5: 75 mg 7.8* (1.8), 150 mg 8.1* (1.3), 300 mg 7.6* (1.4), placebo 0.2 (1.4) [* P <0.05]. For solriamfetol 37.5 mg (OSA only), only MWT2 (≈3 hours post-dose) showed significant change. Common treatment emergent adverse events in both populations included headache, nausea, decreased appetite, anxiety, and nasopharyngitis. Conclusion: Solriamfetol 75 mg in OSA, and 150 and 300 mg in OSA and narcolepsy was associated with sustained improvement in wakefulness, as demonstrated by a time-course effect on MWT, 1 hour through 9 hours post-dosing. Safety and tolerability in both populations were consistent with previous studies of solriamfetol. Support (If Any): Jazz Pharmaceuticals.